Power quality improvement using adaptive unified power quality conditioner - Kwan, Kian Hoong (2012)
In recent years, the prolific use of power electronics devices to improve the overall energy efficiency for electrical systems has led to the deterioration of power quality (PQ) due to harmonic generation. These PQ problems, such as a distorted supply current drawn and a poor power factor at the supply side, have led to severe technical mishaps and substantial economical losses. Likewise, a stable supply voltage has always been desired for smooth operations of many industrial power plants, for example, a petrol chemical plant and a semiconductor plant. Various PQ standards have also been developed to serve as guidelines for stakeholders to adhere to. Compensating devices such as dynamic voltage restorers, uninterruptible power supplies, and active filters are also proposed to handle these PQ problems. Nonetheless, each of these devices has limited capabilities such that they can only handle one or two problems.